IMPORTANCE OF CONSENSUS CULTURE IN IMPLEMENTING THE CONCEPT OF "ENLIGHTENED SOCIETY" IN THE NEW UZBEKISTAN (Scientific journal of the Fergana State University, 2023)
This article highlights the importance of using consensus in the implementation of the concept of "enlightened society" in New Uzbekistan, the realization of the principle of "for human dignity" in the culture of the Uzbek people, and the importance of forming a culture of consensus in the fight against foreign ideas.The relationship between the traditions, customs and values of the Uzbek people with the culture of consensus, the more effective and efficient reforms implemented in the country, the relationship between the state, society and the individual, the role of the culture of consensus in preventing conflicts and its application methods are analyzed.